The dreaming. Volume one, Pathways and emanations - Spurrier, Simon; Gaiman, Neil; Howard, Kat; Hopkinson, Nalo; Watters, Dan (Sandman Universe, 2019)
"One of four books expanding Neil Gaiman's acclaimed Sandman Universe. There is a place where gods are born and stories are spun. Today its walls lie slashed and bleeding. Twenty-three years after he was anointed as its master, the lord of dreams has inexplicably abandoned his domain. Lord Daniel's absence triggers a series of crimes and calamities that consume the lives of those already tangled in his fate. Until he is found, his realm's residents must protect its broken borders alone. But the most senior storytellers are tormented by invasive secrets, the warden Lucien is doubting his own mind, and beyond the gates, something horrific awaits with tooth and talon. Only Dora, the monstrous, finds opportunity in madness, stealing dreams for the highest bidder. But she has no idea how deep the danger lies. Meanwhile, in Daniel's gallery, something new is growing..."--Amazon.com.